AUTONOMOUS SHUTTLES FOR URBAN MOBILITY ON DEMAND APPLICATIONS – ECOSYSTEM DEPENDENT REQUIREMENT ELICITATION. (May 2020) - Grahle, A.; Song, Y.-W.; Brüske, K.; Bender, B.; Göhlich, D.
Abstract: Future transport will change drastically with the introduction of automated vehicles. Here, Autonomous Mobility on Demand (AMoD) will play a major role, requiring a radical change of vehicle design, with many different conceivable concepts. This technology shift holds high potentials and high risks. Uncertainties about future usage profiles, operator and customer requirements have to be dealt with. An approach to elicit initial requirements for future vehicle concepts considering the entire ecosystem is introduced. The applicability is shown for a specific urban mobility scenario.